2012
DOI: 10.1053/j.gastro.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Field Cancerization in the Intestinal Epithelium of Patients With Crohn's Ileocolitis

Abstract: Background & Aims Tumors that develop in patients with Crohn's disease tend be multifocal, so field cancerization (the replacement of normal cells with non-dysplastic but tumorigenic clones) might contribute to intestinal carcinogenesis. We investigated patterns of tumor development from pretumor intestinal cell clones. Methods We performed genetic analyses of multiple areas of intestine from 10 patients with Crohn's disease and intestinal neoplasia. Two patients had multifocal neoplasia; longitudinal sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 43 publications
1
84
0
1
Order By: Relevance
“…Bulk DNA extracts were screened for somatic mutations in genes frequently mutated in colorectal cancers: the APC mutation cluster region (approximately codons 1,250-1,450), KRAS exon 1 (codons 12-13), BRAF (the region around codon 600), and TP53 exons 5-9. Primers and conditions for screening the mutation cluster region of APC are listed in Table S1; otherwise primers and conditions were as previously described (51). Sequences were obtained using BigDye 3.1 cycle sequencing and were run on an ABI 3100 DNA analyzer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk DNA extracts were screened for somatic mutations in genes frequently mutated in colorectal cancers: the APC mutation cluster region (approximately codons 1,250-1,450), KRAS exon 1 (codons 12-13), BRAF (the region around codon 600), and TP53 exons 5-9. Primers and conditions for screening the mutation cluster region of APC are listed in Table S1; otherwise primers and conditions were as previously described (51). Sequences were obtained using BigDye 3.1 cycle sequencing and were run on an ABI 3100 DNA analyzer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…LOH analysis was performed on individual crypt lysates using up to six informative microsatellite markers close to the APC gene (D5S346, D5S2001, and D5S489) and markers on 17p (D17S1832) and 18q (D18S474 and D18S58). Amplification was performed using a multiplexed microsatellite PCR kit (Qiagen) using the primers previously described (51). Fragment analysis was performed on an ABI3100 system (Applied Biosystems), followed by analysis with the Peak Scanner software (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of p53 is helpful to elucidate transformation from inflammation to dysplasia as inflammation does not overexpress p53 [55] . A mutational analyses of multiple areas of intestine from ten patients with CD and intestinal cancer, mutations in KRAS, CDKN2A (p16), and TP53 that were observed in tumor cells was also present in non-tumor, and both nondysplastic and dysplastic epithelium suggestive of a field defect in CD [56] . Another study on 41 patients with CD and small bowel cancer showed dysplasia association in 50% of the patients suggesting an inflammation-dysplasiaadenocarcinoma sequence in CD-related SBA, similar to what is observed in chronic colitis-related colorectal cancer (Figure 1) [55,56] .…”
Section: Crohn's Diseasementioning
confidence: 97%
“…As a recent example, Martincorena and colleagues found putative driver mutations in 18% to 32% of normal, sun-exposed skin cells at a density of 140 driver mutations per square centimeter (Martincorena et al 2015). Patients with inflammatory bowel disease (IBD) are also found to have putative driver mutations in nondysplastic tissue, with mutations in TP53 TSG being detected commonly in patients who subsequently develop cancer (Leedham et al 2009;Galandiuk et al 2012). How can such large numbers of cancer-causing mutations maintain benign phenotypes?…”
Section: Role Of Driver Alterations In Premalignant Evolutionmentioning
confidence: 99%